A Jet Medusa Pendant from Aquincum/Budapest - R. Facsády, Annamária (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
A rare jet cameo-pendant with the representation of a Medusa-head came to light south of the canabae of Aquincum during the excavation of a section of the Roman cemetery. Among the jewellery carved from jet, pendants depicting the head of Medusa form a separate group. We know only 21 pieces without this jewel; all of them are distinctive, unique carvings. The pendant from Aquincum belongs to the group of ‘beautiful-pathetic’ Medusa-heads. It could have been made in the 3rd century, based on analogy and on the other grave-goods. There is a possibility that this type of jewellery was made for burials as an apotropaic object.